Constituintes Químicos dos Zoantídeos Palythoa caribaeorum (Duchassaing & Michelotti, 1860) e Protopalythoa Variabilis (Duerden, 1898) - Almeida, José Gustavo Lima de (2011)
This work describes the chemical composition of the marine species Palythoa caribaeorum and Protopalythoa variabilis, both collected at Paracuru beach, state of Ceará. The cromatographic fractionation of the hexane extract from P. caribaeorum resulted in the isolation of four tetracyclic sterols possessing the ergostan skeleton: 24(R)-ergost-5-en-3b-ol (P-1); 5 a,8a-epidioxy-24(R)-ergost-6-en-3b-ol (P-2); 24(R)- ergost-5-en-3b,7a-diol (P-4) and 24(R)-7a-hydroperoxy-ergost-5-en-3b-ol (P-7), a glycerol derivative, 1-O-hexadecylglycerol (P-3) and four ceramides: N- (2S,3R,4E,8E,1,3-dihydroxy-4,8-octadecadienyl)hexadecanamide (P-5); N- (2S,3R,4E,1,3-dihydroxy-4-octadecenyl)hexadecanamide (P-6); N-[2S,3R,4E,8E,1-(2”- methylamino-ethanosulfonyl)-3-hydroxy-4,8-octadecaenyl]hexadecanamide (P-8) and N-[2S,3R,4E,1-(2”-methylaminoethano-sulfonyl)-3-hydroxy-4-octadecenyl]hexadecanamide (P-9). The cromatographic fractionation of the ethanol extract permited the isolation of a steroid, 24(R)-ergost-7-en-3b,5a,6b-triol (P-10) and a nucleoside 2- methyltimidine (P-11). Column chromatography of the hexane extract of P. variabilis led to the isolation of nonyl hexadecanoate (P-12), the sterol 24(R)-B-norergostan-3b- 5b-diol-6b-carboxylic acid (P-13) and the same chemical constituents previously isolated from P. caribaeorum (P-1, P-2, P-3 e P-4) including the four ceramides (P-5, P-6, P-8 e P-9). The citotoxic and antifungal properties of all ceramides were evaluated, nevertheless none of them showed any activity. All compounds were isolated through adsorption column cromatography over silica gel followed by high performance liquid chromatography. The structures of the isolated compounds were elucidated using spectrometric techniques, such as: GC/MS, HRESIMS, IR and NMR (1H, 13C and 15N) through 1D and 2D pulse sequences and, whenever the case, comparison with literature data